Savvy winner can't believe her luck - Sunday Star, (2012)
KUALA LUMPUR: When Sabah-born Sarah Helmy received a phone call from Proton informing her that she was the lucky winner of a brand new Proton Savvy, the first thought that crossed her mind was that she was being scammed.